Cinema of actuality : Japanese avant-garde filmmaking in the season of image politics - Furuhata, Yuriko, 1973- (Asia-Pacific., 2013)
Cinema of Actuality analyzes Japanese avant-garde filmmakers' struggle to radicalize cinema in light of the intensifying politics of spectacle and a rapidly changing media environment, one that was increasingly dominated by television.